PENGGUNA TATO DI KALANGAN REMAJA KELURAHAN KEMARAYA KECAMATAN KENDARI BARAT - Nirwana Alim; La Janu; La Ode Aris (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2019)
This study aims to determine the reasons for youth in Kemaraya using tattoos and people's views on teenagers who use tattoos. This study uses ethnographic methods and data collection conducted using participant observation and in-depth interviews. The results of this study indicate that several reasons for tattooed adolescents include: (1) family factors such as broken conditions and the existence of teenagers who are far from old age; (2) social environment factors, namely following trends, as accessories (body decoration) and attracting the attention of others. Some community leaders who tend to look positively towards tattoos in adolescents as being like decoration, "body flowers", hobbies and art. There are also negative views from religious leaders, traditional leaders, and adolescents. They impress tattoos with things that are not good, naughty, and prohibited in religion.